Организационные основы формирования свободной экономической зоны в Крыму - Попазогло, Т.В.; Смирнова, Е.А. (Культура народов Причерноморья, 2014)
В статье рассмотрены теоретические аспекты свободной экономической зоны (СЭЗ).
Исследованы организационные основы формирования свободной экономической зоны в Республике Крым и
развитие региона как нового субъекта Российской Федерации. Определены типы свободной экономической
зоны в России, цели и причины создания СЭЗ, а также налоговые льготы для участников СЭЗ на территории
Республики Крым. У статті розглянуто теоретичні аспекти вільної економічної зони (ВЕЗ). Досліджено
організаційні засади формування вільної економічної зони в Республіці Крим та розвиток регіону як нового
суб'єкта Російської Федерації. Визначено типи вільної економічної зони в Росії, мета і причини створення
ВЕЗ, а також податкові пільги для учасників ВЕЗ на території Республіки Крим. In modern conditions the inclusion of the Republic of the Crimea to the Russian Federation is a new stage
of development of economy and industry of the peninsula. One of the ways of development of priority branches of
economy of the Republic of Crimea may be the attraction of investments. Because investing is one of the major
economic institutions, which is most fully realized in the market and increases the investment attractiveness of
industries and economies, allowing increasing the investment potential of companies.
In connection with the adoption of the Crimea in the Russian Federation, the Government considered and adopted the
decision on establishment of the free economic zone on the territory of Crimea for develop and attract investors.
Studied organizational basis for the formation of a free economic zone in the Republic of Crimea and development of
the region as a new subject of the Russian Federation. Identify the types of free economic zones in Russia, goals and
reasons for the creation of the FEZ, as well as tax incentives for FEZ on the territory of the Republic of Crimea.
The establishment and effective organization of activity of free economic zones of the Republic of Crimea, will
contribute to the development of strategic industries in the country and in the region. Will also attract foreign and
domestic investors on favorable terms will be able to carry out their activities and thereby improve the economy of the
Republic of Crimea.
FEZ in the Crimea will operate until 2040 year with the possibility of renewal that will make Republic of Crimea is a
region of high living standards, updated infrastructure and attractive to domestic and foreign investors for their
investments.